Intravenous immunoglobulin treatment during pregnancy and the post-partum period in women with multiple sclerosis: A prospective analysis. Issue 1 (January 2023) - Menascu, Shay; Siegel-Kirshenbaum, Michal; Dreyer-Alster, Sapir; Warszawer, Yehuda; Magalashvili, David; Dolev, Mark; Mandel, Mathilda; Harari, Gil; Achiron, Anat
Background: Relapsing-remitting multiple sclerosis (RRMS) affects predominantly young women within reproductive years. As an increased risk of relapses is known to occur during the post-partum period, it is important to consider treatment options. Aim: Evaluate the effects of intravenous immunoglobulins (IVIg) to prevent post-partum relapses. Methods: We prospectively followed 198 pregnant female RRMS patients, 67 treated with IVIg during pregnancy and the three months post-partum, and 131 untreated patients that served as controls. Results: During the pre-gestation year, 41.4% were treated with immunomodulatory drugs, and 28.3% experienced a relapse. During pregnancy and the post-partum period, the number of relapsing patients significantly decreased in the IVIg group (37.3%, 10.4%, 8.9%, respectively, p = 0.0003), while no significant change was observed in the untreated group (23.7%, 17.6%, and 22.1%). During the three-month post-partum period, there were only mild and moderate relapses in the IVIg group, while in the untreated group, there were also severe relapses. Stepwise logistic regression that assessed the relation between three-month post-partum relapse and explanatory variables demonstrated that untreated patients had increased risk for post-partum relapse (odds ratio = 4.6, 95% CI [1.69, 12.78], p = 0.033). Conclusions: IVIg treatment proved efficient to reduce the rate and severity of relapses during pregnancy and the three-month post-partum.